2018
DOI: 10.2147/phmt.s174789
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of preterm birth at Jimma University Medical Center, southwest Ethiopia

Abstract: BackgroundPreterm birth is the second leading cause of death next to pneumonia in children aged <5 years and the single-most important cause of death in the first month of life. Research examining determinants of preterm birth in Ethiopia is limited. Therefore, this study aimed to determine risk factors associated with preterm births at Jimma University Medical Center in southwest Ethiopia.MethodsThis unmatched case–control study was conducted from March 15 to April 1, 2017 from medical records of mothers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
64
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(104 citation statements)
references
References 16 publications
34
64
1
1
Order By: Relevance
“…The presence of chorio-amnionitis (AOR 3.8; 95% CI: 1.3-10.8) [72] and placenta praevia was correlated with PTB (ARR 3.30, 95% CI: 1.34, 8.14) [79]. The pooled analysis of four studies displayed that history of still birth/abortion was positively associated with PTB (AOR 3.93; 95% CI: 2.70-5.70) [10,37,57,64]. The pooled effects of four studies displayed that history of PTB increased the odds of PTB (AOR 3.45; 95% CI: 2.72-4.38) [10,46,64,69] (Fig.…”
Section: Reproductive Health Factorsmentioning
confidence: 97%
See 2 more Smart Citations
“…The presence of chorio-amnionitis (AOR 3.8; 95% CI: 1.3-10.8) [72] and placenta praevia was correlated with PTB (ARR 3.30, 95% CI: 1.34, 8.14) [79]. The pooled analysis of four studies displayed that history of still birth/abortion was positively associated with PTB (AOR 3.93; 95% CI: 2.70-5.70) [10,37,57,64]. The pooled effects of four studies displayed that history of PTB increased the odds of PTB (AOR 3.45; 95% CI: 2.72-4.38) [10,46,64,69] (Fig.…”
Section: Reproductive Health Factorsmentioning
confidence: 97%
“…The pooled effects of four studies illustrated that birth interval less than 24 months was positively associated with PTB (AOR 2.03; 95% CI: 1.57-2.62) [10,57,63,74]. The pooled analyses of four studies (AOR 5.52; 95% CI: 4.32-7.05) [37,38,52,72] and three studies (AOR 5.77, 95% CI 4.27-7.79) [7,38,57] showed that ANC visits < 4 and absence of ANC increased the risk of PTB, respectively. The pooled effects of two studies identified that multiple pregnancy was positively associated with PTB (AOR 3.44; 95% CI: 3.02-3.91) [57,79] (Fig.…”
Section: Reproductive Health Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 10 studies that assessed the association of short birth interval with preterm birth in Sub-Saharan African countries were included in this review. Five of the included studies were conducted in Ethiopia (18)(19)(20)(21)(22), two in Tanzania (23,24), two in Kenya (25,26), and one in Ghana (27). Of the ten studies two were cohort study (20,24), ve case-control (18,(21)(22)(23)27) and three cross-sectional (19,25,26).…”
Section: Included Study Characteristicsmentioning
confidence: 99%
“…The risk factors for preterm birth were; hypertensive disorders of pregnancy, maternal height < 1.50 m, PROM, anemia, urethral tract infection, maternal age < 20, birth interval < 2 years and multiple pregnancy were signi cantly associated with preterm birth (PTBs) (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%